The Analysis of Pre-Merger and Post-Merger of Good Corporate Governance Implementation in PT CIMB Niaga Tbk - Winanda, Astri (Jurnal KIAFE, 2021)
This study aims to examine the performance of Good Corporate Governance in merger companies. This study would like to outline the difference between pre-merger and post-merger Good Corporate Governance Performance. This study uses secondary data obtained from annual report of PT CIMB Niaga listed in Indonesia Stock Exchange (IDX) from 2007-2020. The author uses qualitative coding method in analyzing the data. Data analysis uses is content analysis design to analyze and understanding the text. The result of this study shows that merger give positive impact in Good Corporate Governance growth.